PERANCANGAN ULANG TATA LETAK FASILITAS DENGAN MEMPERHATIKAN ASPEK ERGONOMI LINGKUNGAN - Putu Eka Dewi Karunia Wati (UPPM Akademi Komunitas Semen Indonesia, 2019)
CV. Mandiri Jaya Logam is a metal smelting that produces aluminum bars with a production capacity of 300 - 350 kg / day where the average weight of each aluminum bar weighs 4.3 kg. This UKM has a production area of ??15m x 6m where the area where the production is very irregular and not ergonomic both from the work environment and working conditions. The irregular location of raw materials and the location of the furnace that is far from the mold makes the bucket must be heated repeatedly so that the work becomes inefficient. Therefore it is necessary to design an ergonomic production space layout that can facilitate the production process, providing comfort to workers in doing work so that productivity will increase. This research will provide the best layout of a number of alternative layouts seen from the moment of material transfer. The layout chosen is the one that has the lowest material transfer moment. In addition, the level of productivity will be measured based on the number of products that can be produced.